2014
DOI: 10.1155/2014/458296
|View full text |Cite
|
Sign up to set email alerts
|

Visual Outcomes and Patient Satisfaction after Refractive Lens Exchange with a Single-Piece Diffractive Multifocal Intraocular Lens

Abstract: Purpose. To report visual outcomes and patient satisfaction after unilateral or bilateral refractive lens exchange (RLE) with a single-piece bifocal diffractive multifocal intraocular lens (MIOL). Methods. All patients underwent RLE with the ZMB00 MIOL (Abbott Medical Optics). Patient charts were reviewed to evaluate the distance, intermediate, and near visual acuity (VA), contrast sensitivity, extent of visual symptoms (0–5), satisfaction (1–5), and rate of spectacle independence between unilateral and bilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 32 publications
2
22
2
3
Order By: Relevance
“…For the near vision, the current mean DCNVA of 20/27 in the operated eyes was similar to the previously reported values of other bifocal MIOLs with +3- to +4-D near addition in post-LASIK eyes (range, 20/26 to 20/20) [1416, 18] and eyes with virgin cornea (range, 20/25 to 20/20) at 30 to 40 cm [3, 4, 33]. The intermediate vision of bifocal MIOLs is weak [38].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…For the near vision, the current mean DCNVA of 20/27 in the operated eyes was similar to the previously reported values of other bifocal MIOLs with +3- to +4-D near addition in post-LASIK eyes (range, 20/26 to 20/20) [1416, 18] and eyes with virgin cornea (range, 20/25 to 20/20) at 30 to 40 cm [3, 4, 33]. The intermediate vision of bifocal MIOLs is weak [38].…”
Section: Discussionsupporting
confidence: 88%
“…Compared to our previous study [4] of the ZMB00 in eyes with virgin cornea, the operated eyes in the current study had significantly worse CS at spatial frequency of 3 cpd ( P = 0.009; Mann–Whitney U test). This suggested that visual quality with the ZMB00 could be affected by LASIK and may be explained by the increased SA after LASIK that was not fully compensated.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations